Health belief model in predicting treatment intention among healthy and gynecologic cancer women with sexual dysfunction: Structural equation modeling - Yin Jou Chou; Chun Ming Shih (Elsevier, 2022)
Objective: Few large-scale studies have focused on the effect of gynecologic cancer compared with other biopsychosocial factors on willingness to seek treatment among women with sexual dysfunction. The aim of study was to identify predictors of the intention to treat female sexual dysfunction (FSD) among sociodemographic factors, physiologic factors, psychologic factors, gynecologic cancer, and health belief model (HBM). Materials and methods: This study was a cross-sectional, hospital-based survey conducted from October 2013 to September 2019. Participants included healthy women and gynecologic cancer survivors who were aged 20 years or older and had been in a monogamous relationship for at least 12 months. They were enrolled in the gynecologic departments in southern Taiwan. Those who met DSM-5 criteria of sexual dysfunction were analyzed with Structural equation modeling. Intention to seek treatment was the primary outcome. Results: 448 of 643 women met DSM-5 sexual dysfunction. The mean age was 42.0 years (range: 21.8-68.1 years). Fifty-eight percent of women reported sexual treatment intention. The model fit was good: χ2 = 367.42, P < .001, χ2/df = 2.83, CFI = 0.933, TLI = 0.921, and RMSEA = 0.066 (95%CI: 0.058-0.074). Perceived severity, perceived benefits, perceived barriers, cue to action, self-efficacy and university education at least significantly predicted treatment intention. There were no significant differences in treatment intention regarding age and gynecologic cancer. Self-efficacy was the strongest predictor, which directly affected treatment intention (P = .001). Perceived severity was the second strongest predictor, mainly affecting treatment intention indirectly (P = .01). Perceived barriers was the third strongest predictor (P = .001), indirectly and negatively affected treatment intention. Conclusions: Five out of six HBM factors and university education at least could significantly predict the intention to treat FSD. Gynecologic cancer was not a significant predictor.